Role of calcium-independent phospholipase A 2 in the pathogenesis of Barth syndrome - Ashim Malhotra; Irit Edelman‐Novemsky; Yang Xu; Heide Plesken; Jinping Ma; Michael Schlame; Mindong Ren (2009)
Quantitative and qualitative alterations of mitochondrial cardiolipin have been implicated in the pathogenesis of Barth syndrome, an X-linked cardioskeletal myopathy caused by a deficiency in tafazzin, an enzyme in the cardiolipin remodeling pathway. We have generated and previously reported a tafazzin-deficient Drosophila model of Barth syndrome that is characterized by low cardiolipin concentration, abnormal cardiolipin fatty acyl composition, abnormal mitochondria, and poor motor function. Here, we first show that tafazzin deficiency in Drosophila disrupts the final stage of spermatogenesis, spermatid individualization, and causes male sterility. This phenotype can be genetically suppressed by inactivation of the gene encoding a calcium-independent phospholipase A 2 , iPLA2-VIA, which also prevents cardiolipin depletion/monolysocardiolipin accumulation, although in wild-type flies inactivation of the iPLA2-VIA does not affect the molecular composition of cardiolipin. Furthermore, we show that treatment of Barth syndrome patients' lymphoblasts in tissue culture with the iPLA 2 inhibitor, bromoenol lactone, partially restores their cardiolipin homeostasis. Taken together, these findings establish a causal role of cardiolipin deficiency in the pathogenesis of Barth syndrome and identify iPLA2-VIA as an important enzyme in cardiolipin deacylation, and as a potential target for therapeutic intervention.